Gender Issues in Business and Economics Selections from the 2017 Ipazia Workshop on Gender (Springer Proceedings in Business and Economics,, 2018)
This volume presents current research on gender studies in the specific context of the knowledge economy. Featuring contributions from the 2017 Annual Ipazia, the Scientific Observatory for Gender Studies Workshop on Gender, this book investigates gender issues and female entrepreneurship from social, economic, corporate, organizational, and management perspectives, with particular emphasis on advancing the understanding of gender in business and economic research. The post-industrial knowledge economy is characterized by an emphasis on human capital as the real engine of sustainable growth and development. With women comprising an increasing share of the global workforce, gender studies play a central role in exploring and understanding the attitudes and skills of women in business and their impact on economic and social development. Gender inequality in public and private contexts is decreasing due to an increase of women in leadership roles in business, the expansion and diversity of females in education, and a larger presence of women in policymaking roles. Ipazia, the Scientific Observatory for Gender Studies, aims to define an updated framework of research, service and projects on women and gender relations to highlight the evolution of gender in business and economics. This volume features contributions on female-owned family business, gender diversity in organizations, gender capital, and immigration from the 2017 Ipazia workshop.